Investigation of high temperature corrosion resistance of Ni25Cr coated and bare 347H SS in actual husk fired boiler atmosphere. (January 2020) - Gada, Hannan; Mudgal, Deepa; Parvez, Saad; Ahmad, Babar
Highlights: Corrosion run for bare and Ni25Cr coated 347H SS was conducted in husk fired boiler. Detonation gun was used to deposit coating on 347H stainless steel. Bare 347H SS suffered from severe corrosion. Coating provides substantial protection by forming oxides of NiCr2 O4 and Cr2 O3 . Abstract: This paper presents the experimental investigation of corrosion occurring at elevated temperatures in various critical constructional components of husk-fired boiler. In order to reduce the impact of high operating temperatures on boiler components, some protection, in the form of high temperature resistant coating becomes necessary. The critical components of a boiler are generally made of stainless steel. In this work an attempt has been made to determine experimentally the corrosion resistance performance of 347H SS components coated with 75Ni25Cr. Specimens of 75Ni25Cr coated 347H SS and bare 347H SS were hung in an actual husk fired boiler near superheater region through soot blower dummy points. The temperature recorded by an industrial pyrometer near superheater region was about 750 ± 50 °C. These samples were hung for about 150 h in the above-mentioned environment and it was found that 75Ni25Cr coating offers substantial protection as the bare metal underwent severe corrosion.